Keterampilan Guru dalam Mengelola Kelas Rendah dalam Pembelajaran Tematik di SDN 19 Aceh Barat - Eva Yuliana (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
Managing classes is an activity carried out by teachers aimed at creating classroom conditions that allow the optimal learning process to take place. For this reason, teachers as the front guard in implementing learning are required to master a number of skills in managing classes. The purpose of this study is to assess and analyze the skills of teachers in managing low grades on thematic learning. This study uses a qualitative approach with an observation method. Data collection techniques are carried out by tracing various sources, in the form of government documents, mass media, and relevant research results and supported by the results of interviews conducted with several low-grade teachers who were then analyzed using policy research. The results of this study indicate that the skills of teachers in managing low grades consist of 1) skills related to the creation and development of optimal learning conditions, which include aspects of responsiveness, dividing attention, and concentration; 2) skills related to the development of optimal learning conditions, related to the obstacles that occur during the learning process caused by student behavior. regarding this, the teacher can use the following strategies as an action to improve student behavior, which consists of behavior modification; and a Group problem-solving approach. Thus, the learning process can run effectively and efficiently, so that the competencies expected to be mastered by learners and learning objectives can be achieved.